TiO2 nanotubes zeolite nanophotocatalyst performance efficacy toward the photocatalytic degradation of triclocarban in bathroom greywater - Arifin, Siti Nor Hidayah A; Radin Mohamed, Radin Maya Saphira; Abu Talib, Mohd Khaidir; Mohd Asharuddin, Syazwani; Mohd Apandi, Najeeha; Hairuddin, Nur Diyana (taylor & francis, 2025)
Triclocarban (TCC) is persistent in aquatic environments, where it can remain stable for extended periods. It can cause long-term exposure, potentially affecting ecosystems and human health through contaminated fish or water. Therefore, this study aims to investigate the degradation of TCC in bathroom greywater by the application of TiO2 nanotubes coated with zeolite (TNZPC) in photocatalytic degradation. Electrochemical anodization (ECA) and electrophoretic deposition (EPD) were applied to form TNZPC. Field Emission-Scanning Electron Microscopy (FESEM), Energy Dispersive Spectroscopy (EDS), X-ray Diffraction (XRD), and X-ray Fluorescence (XRF) verified the characterization of TNZPC accordingly and the degradation kinetics of TCC followed the pseudo-first-order model of Hinshelwood. The highest degradation rate, reaching 95.2%, was observed at pH 11, while the lowest rate was at pH 3, with a degradation efficiency of only 72.6% after 60minutes of irradiation with utilization of 0.75cm2 of TNZPC. The mechanism study has verified eleven intermediate products were produced during TCC degradation by the process of oxidation, ozonation, hydroxyl radical (*OH), and dichlorination. The study suggests that finding the optimum conditions such as photocatalyst modification, cationic material, light sources, TCC initial concentration, pH, and TNZPC size play crucial roles in significant TCC photocatalytic degradation.